Formation of Identity and Sexual Orientation of Young Filipino Bisexuals: An Interpretative Phenomenological Analysis - Geonanga, Kristian Ed G. (Animo Repository, 2018)
Topics concerning LGBT, specifically bisexuals, are not as widely researched like that of topics concerning heterosexuals. Hence, little is known about LGBT individuals. However, due to some researches that are conducted by various advocates, organizations, and researchers, many aspiring researchers aim to explore the topics concerning LGBT like identity and sexual orientation. Thus, this research aims to explore the formation of identity and sexual orientation of young Filipino bisexuals, specifically, to formulate a formation of identity and sexual orientation of young Filipino bisexuals model that is drawn from the experiences, perceived origin of bisexuality, and factors affecting identity formation of the participants. This study utilized an interpretative phenomenological analysis, qualitative research design, and thematic analysis to analyze the gathered data. Five bisexual participants were chosen using purposive homogenous sampling technique. The result of the study showed that there are five stages of formation of identity and sexual orientation of bisexuals. There are Stage 1: disorientation of sexuality, Stage 2: deconstruction of the self, Stage 3: revelation of sexuality to interpersonal relationships, Stage 4: rationalization of bisexuality and reaching out towards other LGBT, and Stage 5: reconstruction of the self. Moreover, the perceived origins of bisexuality of the research participants were based on the principles of nature and nurture. In addition, the factors that affected their identity formation were: society, family, stigma/discrimination, culture, peers, social media, work, self, and internalized sexual stigma.